Pharmacokinetic Engineering of OX40-Blocking Anticalin Proteins Using Monomeric Plasma Half-Life Extension Domains - Siegemund, Martin; Oak, Prajakta; Hansbauer, Eva-Maria; Allersdorfer, Andrea; Utschick, Karoline; Winter, Alexandra; Grasmüller, Christina; Galler, Gunther; Mayer, Jan-Peter; Weiche, Benjamin; Prassler, Josef; Kontermann, Roland E.; et al. (Frontiers in Pharmacology, 2021)
Anticalin® proteins have been proven as versatile clinical stage biotherapeutics. Due to their small size (~20 kDa), they harbor a short intrinsic plasma half-life which can be extended, e.g. by fusion with IgG or Fc. However, for antagonism of co-immunostimulatory tumor necrosis factor receptor superfamily (TNFRSF) members in therapy of autoimmune and inflammatory diseases, a monovalent, pharmacokinetically optimized Anticalin protein format that avoids receptor clustering and therefore potential activation is favored. We investigated the suitability of an affinity-improved streptococcal albumin-binding domain (ABD) and the engineered Fab-selective immunoglobulin-binding domain (IgBD) SpGC3Fab for plasma half-life extension (HLE) of an OX40-specific Anticalin and bispecific Duocalin proteins, neutralizing OX40 and a second co-immunostimulatory TNFRSF member. The higher affinity of ABD fusion proteins to human serum albumin (HSA) and mouse serum albumin (MSA), with a 4 to 5-order of magnitude lower KD compared with the binding affinity of IgBD fusions to human/mouse IgG, translated into longer terminal plasma half-lives (t1/2). Hence, the anti-OX40 Anticalin-ABD protein reached t1/2 values of ~40 h in wild-type mice and 110 h in hSA/hFcRn double humanized mice, in contrast to ~7 h observed for anti-OX40 Anticalin-IgBD in wild-type mice. The pharmacokinetics of an anti-OX40 Anticalin-Fc fusion protein was the longest in both models (t1/2 of 130 h and 146 h, respectively). Protein formats composed of two ABDs or IgBDs instead of one single HLE domain clearly showed longer presence in the circulation. Importantly, Anticalin-ABD and -IgBD fusions showed OX40 receptor binding and functional competition with OX40L-induced cellular reactivity in the presence of albumin or IgG, respectively. Our results suggest that fusion to ABD or IgBD can be a versatile platform to tune the plasma half-life of Anticalin proteins in response to therapeutic needs.